1985
DOI: 10.2307/1940553
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Exclusion of Aphytis lingnanensis by A. melinus: Potential Role of Host Size

Abstract: Aphytis melinus, an ectoparasitoid of California red scale, Aonidiella aurantii, replaced A. lingnanensis, another ectoparasitoid, in certain California citrus areas during the 1960's following the form~r's introdu~tion i~ _1956-1957. We show that, although both species attack a similar range o~ host slZes, A. melm~ _utiltz:s a smaller threshold scale size for the production of daughters. Size differences of scales Withm a cttrus tree (largest scales occur on fruits, smallest on wood, and intermediate on leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 20 publications
3
96
1
1
Order By: Relevance
“…The displacement of the native asexual gecko Lepidodactylus lugubris by the introduced sexual species Hemidactylus frenatus in the tropical Pacific (Case et al 1994;Petren and Case 1996) and that of Aphytis lingnanensis, a parasitoid of the red scale (Aonidiella aurantii), by its congener Aphytis melinus in southern California (Luck and Podoler 1985;Murdoch et al 1996) provide some of the more well studied examples. These observations suggest that, in some cases at least, spatial processes cannot counteract competitive exclusion because of insufficient spatial variance in competitive ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The displacement of the native asexual gecko Lepidodactylus lugubris by the introduced sexual species Hemidactylus frenatus in the tropical Pacific (Case et al 1994;Petren and Case 1996) and that of Aphytis lingnanensis, a parasitoid of the red scale (Aonidiella aurantii), by its congener Aphytis melinus in southern California (Luck and Podoler 1985;Murdoch et al 1996) provide some of the more well studied examples. These observations suggest that, in some cases at least, spatial processes cannot counteract competitive exclusion because of insufficient spatial variance in competitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, one would expect such large-scale exclusion to occur when competitive ability is determined by traits that are fixed within and across populations. For example, A. melinus gains a competitive advantage over A. lingnanensis because of a life-history difference; A. melinus is able to obtain female offspring from a smaller-sized scale than A. lingnanensis (Luck and Podoler 1985). Using a stage-structured host-parasitoid model, Murdoch et al (1996) showed that this subtle difference is sufficient to explain the rapid displacement of A. lingnanensis from inland areas of southern California.…”
mentioning
confidence: 99%
“…Butternut) (Raciti et al, 2003). In order to keep background parasitism by naturally occurring A. melinus low, the trial was carried out in a period (June-July) when the parasitoid is scarce in the field (Lizzio et al, 1998;Siscaro et al, 1999) and California red scale is mainly present as virgin females, which is the preferred instar of the parasitoid (Luck & Podoler, 1985;Heimpel et al, 1997;Pekas et al, 2010a).…”
Section: Insect Releasesmentioning
confidence: 99%
“…Heavily infested fruit may be downgraded in the packinghouse and, if population levels are high, trees can be seriously damaged. Aphytis melinus effectiveness could depend on the scale careful monitoring, on the use of selective insecticides to control other pests (Grafton-Cardwell et al, 2006;Suma et al, 2009;Planes et al, 2012;Vanaclocha et al, 2012), on the host instars available and their size (Luck & Podoler, 1985;Pekas et al, 2010a), on ant activity (James et al, 1997;Pekas et al, 2010b), on the fitness of the released insects (Vasquez & Morse, 2012) or on environmental conditions (DeBach & Sisojevic, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…About 20% of the male scales are allocated a female Aphytis. About 70% of the third instar female scales are allocated a female Aphytis offspring, about 25% are allocated a male Aphytis offspring and about 5% are allocated two Aphytis offspring (usually a male and a female) (Luck et al, 1982;Luck and Podoler, 1985). The two eggs are laid during the same host visit and represent a case of gregariousness (Luck et al, 1982).…”
Section: Aphytis Life Historymentioning
confidence: 99%